2015
DOI: 10.1002/cplx.21656
|View full text |Cite
|
Sign up to set email alerts
|

Global chaotic parameters of heart rate variability during mental task

Abstract: We aimed to evaluate the novel chaotic global techniques of heart rate variability (HRV) analysis during a specific autonomic test, the mental arithmetic overload test. These are spectral detrended fluctuation analysis and spectral multi-taper method; in addition to spectral entropy. We analyzed 24 healthy male students-all nonsmokers, aged between 18 and 22 years old. HRV was analyzed in the following periods: control protocol-the 10-min periods before the performance of the task and the 5-min periods during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
0
6
0
1
Order By: Relevance
“…A previous study reported that chaotic global analysis was unable to identify HRV changes during mental task [59]. Another research study investigated chaotic global analysis in RR intervals during exposure to heavy metal music [60].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that chaotic global analysis was unable to identify HRV changes during mental task [59]. Another research study investigated chaotic global analysis in RR intervals during exposure to heavy metal music [60].…”
Section: Discussionmentioning
confidence: 99%
“…Entropy-based techniques are routinely employed in analysis of medical data especially cardiovascular [17][18][19], respiratory [20,21] and neurological signals [22,23]. In this case, the cardiovascular system that composes the dynamical systems was scrutinized in obese and non-obese children.…”
Section: Entropic Categoriesmentioning
confidence: 99%
“…Entropy-based techniques are routinely employed in analysis of medical data especially cardiovascular [29,30], respiratory [31,32] and neurological signals [33,34]. A low entropy dataset is highly predictable -whereas a high entropy dataset is less predictable.…”
Section: Methodsmentioning
confidence: 99%